The neuro-image : a Deleuzian film-philosophy of digital screen culture - Pisters, Patricia (Cultural memory in the present., 2012)
Arguing that today's viewers move through a character's brain instead of looking through his or her eyes or mental landscape, this book approaches twenty-first-century globalized cinema through the concept of the "neuro-image." Pisters explains why this concept has emerged now, and she elaborates its threefold nature through research from three domains--Deleuzian (schizoanalytic) philosophy, digital networked screen culture, and neuroscientific research. These domains return in the book's tripartite structure. Part One, on the brain as "neuroscreen," suggests rich connections between film theor.